Short Communication: Agricultural biodiversity and economic productivity of the yards in Arguni Bawah, Kaimana District, West Papua Province, Indonesia - ALFRED ALFONSO ANTOH; NURHAYATI HS ARIFIN; M A CHOZIN; HADI SUSILO ARIFIN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Antoh AA, Arifin NHS, Chozin MA, Arifin HS. 2019. Agricultural biodiversity and economic productivity of the yards in Arguni Bawah, Kaimana District, West Papua Province, Indonesia. Biodiversitas 20: 1020-1026. Papua Island, Indonesia has abundance of agricultural biological resources. This is reflected in a variety of agricultural products in different parts of the area and in the use of yards, which is not fully utilized. This study was aimed at mapping the agricultural biodiversity of the yards, as well as measuring their economic productivity. The study area was Arguni Bawah Sub-district, Kaimana District, West Papua Province, Indonesia, and the study was conducted from November 2017 to March 2018. The average number of plant species recorded from yards were 13, number of individuals being 72 in an average yard size of 696 m2. The smallest yard was 231 m2 with only three species and 4 individuals. The maximum number of species found were 26 with 267 individuals. The maximum size of yards studied was 3,000 m2. There are five functional types of plants with high density and SDR, there are the species producing starch (taro and banana), vegetables (gedi and spinach), fruits (banana) and ornamentals, among others. The Shanon-Wiener diversity index (H´) ranged from 1.8 to 2.5, indicating that the biodiversity of plant species in the yards may be interpreted as abundant or moderate. The evaluation of economic productivity showed that average cash income received by households from yards was Rp.7,693,000.